Layering, Kludgeocracy and Disability Rights: The Limited Influence of the Social Model in American Disability Policy. Issue 1 (30th October 2017) - Burke, Thomas F.; Barnes, Jeb
Abstract : The United States has been a leader in the creation of disability rights law, providing a policy template for other nations. Yet the social model, the animating philosophy behind the disability rights movement, has had little effect on the wide range of welfare programs that serve people with disabilities. These programs, whose creation preceded the modern disability rights movement, reflect a medical model of disability that is at odds with the social model. Analysing the Americans with Disabilities Act (which embodies the social model) and Social Security Disability Insurance (the largest welfare program for people with disabilities), we explore how and why this layering of contradictory disability rights and welfare programs developed and how it has been maintained. We argue that the tension between these policies engendered a series of patches, or 'kludges', that allow the policies to coexist without meaningful synthesis. We contend that the United States is particularly prone to this layering of 'tense policies', but that it is likely characteristic of disability policy in many nations. Finally we argue that accurate benchmarking of disability rights regimes across nations requires analysts to dig through all the layers of disability policy.